Characterization of the cellular and molecular profiles of CDH1-re-expressed Breast Adenocarcinoma Cells (MDA-MB-231) treated with Zebularine and Trichostatin A followed by Tumour Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL) - Wong, Sonia How Ming (2020)
Breast cancer (BC) is a heterogeneous disease of which its definite cure had yet to be discovered. Tumour Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL) is one potential anti-cancer protein with its selective killing on cancerous cells while largely evading the healthy cells. Nonetheless, many cancer cells have built TRAIL resistance, including breast cancer. In this study, the addition of two epigenetic drugs, Trichostatin A (TSA) and Zebularine (Zeb) combined prior to TRAIL treatment (TZT) was shown to induce significant increase in G0/G1 cell cycle arrest in MDA-MB-231 (57.78%). With E-cadherin expression, the G0/G1-arrested population increased to 74.2% (231-EGFP) and 83.15% (MCF-7). Moreover, TZT had also significantly reduced cell viability of 231-EGFP to 62.12%. The observed cell inhibitory effects might be due to suppression of proliferating cell nuclear antigen (PCNA) and cyclin-dependent kinase 2 (CDK2) mRNA expression. The TZT-induced cell cycle arrest had also driven apoptosis occurrence and it was supported by the up-regulation of p21 and p-p53 (S392) proteins in MDA-MB-231 by TZT. With the in vitro re-expression of E-cadherin in 231-EGFP, down-regulation of anti-apoptotic PON2, Catalase, Clusterin, IAPs as well as cell stress proteins had validated the notion that E-cadherin expression enhances the TZT anti-cancer efficacy. Similarly, in E-cadherin-positive MCF-7, TZT treatment had down-regulated the anti-apoptotic proteins, increased the pro-apoptotic SMAC, HTRA2 as well as both the TRAIL receptors, TRAIL-R1 and -R2. On the other hand, the TZT treatment regime had negligible effect on reducing the cell migration rate of the invasive MDAMB-231 and 231-EGFP cell lines. This was supported by the lack of pro-invasive matrix metalloproteinase 9 (MMP9) down-regulation by the TZT treatment. Therefore, our study showed that TSA and Zeb are potential sensitizers of breast cancer towards TRAIL-induced cell inhibition, cell cycle arrest leading towards apoptosis while having no tangible anti-invasive potential. Nonetheless, from our ex vivo findings, TRAIL-R2, TRAIL and E-cadherin markers’ anti-cancer functions had been hijacked by BC cells to facilitate their survival (TRAIL) and metastatic potential (TRAIL-R2, E-cadherin). Thus, these markers’ over-expression and localization can potentially serve as markers for BC prognosis and treatment regime selection.